2010
DOI: 10.1099/vir.0.023374-0
|View full text |Cite
|
Sign up to set email alerts
|

A bifunctional anti-enterovirus compound that inhibits replication and the early stage of enterovirus 71 infection

Abstract: Enviroxime is an anti-enterovirus compound that targets viral protein 3A and/or 3AB and suppresses a replication step of enterovirus by an unknown mechanism. To date, a number of anti-enterovirus compounds that have little structural similarity to enviroxime but induce common resistance mutations in the 3A-encoding region have been identified. The present study identified a novel type of functionally enviroxime-like compound, AN-12-H5. This compound had no structural similarity to enviroxime or to known enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…We found that the viral RNAs from both plaques contained one nucleotide substitution, G5318A, resulting in an amino acid change from alanine to threonine in the 3A sequence. The same mutation was reported previously to confer resistance to a diverse class of so-called enviroxime-like compounds, believed to target a PI4KIII␤-dependent step in the viral replication cycle (10,(43)(44)(45)(46). We confirmed that this mutation was responsible for the resistance to E7(2) by genetically engineering the corresponding change into the poliovirus genome (not shown).…”
Section: E7(2) Affects Binding Of Cellular and Viral Factors To Membrsupporting
confidence: 72%
“…We found that the viral RNAs from both plaques contained one nucleotide substitution, G5318A, resulting in an amino acid change from alanine to threonine in the 3A sequence. The same mutation was reported previously to confer resistance to a diverse class of so-called enviroxime-like compounds, believed to target a PI4KIII␤-dependent step in the viral replication cycle (10,(43)(44)(45)(46). We confirmed that this mutation was responsible for the resistance to E7(2) by genetically engineering the corresponding change into the poliovirus genome (not shown).…”
Section: E7(2) Affects Binding Of Cellular and Viral Factors To Membrsupporting
confidence: 72%
“…Moderate anti-HCV activity was observed for enviroxime at high concentrations, consistent with a recent report (23), possibly due to its nonspecific anti-PI4KA activity. These results suggested that T-00127-HEV2 is a novel minor enviroxime-like compound, along with AN-12-H5 (22,36).…”
Section: Resultsmentioning
confidence: 78%
“…Recently, itraconazole was identified as another minor enviroxime-like compound (37). The characteristic properties of minor enviroxime-like compounds are (i) weak resistance of a PV mutant with a G5318A mutation compared to that observed for the major group (around 5-fold increase of PV replication versus Ͼ50-fold increase of PV replication) and (ii) anti-hepatitis C virus (HCV) activity (22,36). This suggested a common replication pathway inhibited by minor enviroxime-like compounds in enterovirus and HCV, possibly related to PI4P production, which depends on different PI4 kinases: PI4KB in enterovirus and PI4KA in HCV replication (20,22,38,39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs that target host factors that are crucial for virus replication are believed to impede this process. In recent years, several studies identified the essential membrane-modifying host cell factor phosphatidylinositol-4-kinase III␤ (PI4KIII␤) as the target of broad-spectrum and highly potent inhibitors of enterovirus replication (1)(2)(3)(4)(5)(6)(7)(8). However, following lengthy selection processes, coxsackievirus B3 (CVB3) mutants that are resistant to these inhibitors emerged and were shown to harbor single point mutations in the nonstructural protein 3A (4,7,8).…”
mentioning
confidence: 99%